Sistem Kendali Pengaturan Suhu Kandang Ayam berbasis Mikrokontroler - Arya, Muhammad Hernan; Zainal, Muhammad (Jurnal Mosfet, 2024)
The current chicken coop temperature control system still uses a semi-automatic control system, handling problems such as sudden temperature changes, making it difficult to handle quickly. This study aims to regulate the temperature of the chicken coop according to the age temperature of the chicken so that it remains stable. This research uses an experimental method. It uses an Arduino IDE for programming, and uses a DHT11 temperature sensor, an Arduino Uno Atmega328, a 16x2 LCD, an RTC and a 4 Chanel Relay Module that can be controlled automatically. The results of the study show that this tool works well and works continuously, if the age of the chicken is 1-5 days with a temperature of more than 30°C, the fan rotates to lower the temperature of the chicken coop and if the temperature is less than 29°C, the fan turns off and the heater turns on to stabilize the temperature. Chicken age 6-10 days If the temperature is more than 28°C then the fan is on to lower the temperature and if the temperature is less than 27°C then the fan is off and the heater is on. The age of the chicken is 11-30 days, if the temperature is more than 26°C, the fan is turned on to lower the temperature and if the temperature is less than 25°C, the fan is off and the heater will turn on to stabilize the temperature again.